In vivo and in vitro Approach to Anti-arthritic and Anti-inflammatory Effect of Crocetin by Alteration of Nuclear Factor-E2-Related Factor 2/hem Oxygenase (HO)-1 and NF-κB Expression - Li, Yi; Kakkar, Rajat; Wang, Jian (Frontiers in Pharmacology, 2018)
Crocetin (apo carotenoid dicarboxylic acid) is a common constituent of saffron. Its importance is well documented in Chinese medicine. Some studies have reported the inhibitory effect on inflammation in rats. The aim of the current experimental investigation to scrutinize the anti-inflammatory effect of Crocetin using the lipo polysaccharide (LPS) induced mouse macrophages (RAW 264.7) in vitro and complete Freund’s adjuvant-induced arthritis model and to explore in vivo possible mechanism of action. RAW 264.7 macrophages were used for estimation of the effect of crocetin on the cyclooxygenase (COX-2), nitric oxide (NO)production, anti-inflammatory and along with pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), and interleukin-10 (IL-10). Single intraperitoneal injection of complete freund’s adjuvant (CFA) was used to induce arthritis. The rats were divided into different group and received the oral administration of crocetin in a dose-dependent manner with indomethacin till 28 days. The paw edema and body weight was estimated at regular interval of time. The biochemical parameters, hematological and pro-inflammatory cytokines such as tumor necrosis factor receptor 1 (TNF-R1), IL-6, and IL-1β, Vascular endothelial growth factor (VEGF); heme oxygenase-1/nuclear factor erythroid 2–related factor 2 (HO-1/Nrf-2) expression were estimated at end of the experimental study. Crocetin inhibited the COX-2 catalyzed prostaglandin (PGE2) and inducible nitric oxide synthase catalyzed NO production on RAW 264.7. The paw edema and body weight was significantly (P < 0.001) modulated by the Crocetin in a dose-dependent manner. Crocetin treatment increased the level of red blood cells (RBC), hemoglobin (Hb) and decreased level of white blood cells (WBC), erythrocyte sedimentation rate (ESR), alkaline phosphatase (ALP), serum glutamic pyruvic transaminase (SGPT), and serum glutamic-oxaloacetic transaminase (SGOT) parameters, with reduction of TNF-α, IL-6, and IL-1β.The protective effect of crocetin was substantiated with a reduction in expression of IL-6, IL-1β, VEGF, and TNF-R1, respectively. Crocetin also increased the HO-1/Nrf-2 and decreased the nuclear factor kappa-B (NF-κB) mRNA, protein expression. On the basis of the result, we can conclude that the reduction of HO-1/Nrf-2 expression, as well as inflammatory mediators, may be involved in the protective effect of Crocetin in the CFA model.